2006
DOI: 10.1103/physrevb.73.224115
|View full text |Cite
|
Sign up to set email alerts
|

Origin of intergranular embrittlement of Al alloys induced by Na and Ca segregation: Grain boundary weakening

Abstract: Using a first-principles computational tensile test, we show that the ideal tensile strength of an Al grain boundary ͑GB͒ is reduced with both Na and Ca GB segregation. We demonstrate that the fracture occurs in the GB interface, dominated by the break of the interfacial bonds. Experimentally, we further show that the presence of Na or Ca impurity, which causes intergranular fracture, reduces the ultimate tensile strength when embrittlement occurs. These results suggest that the Na/ Ca-induced intergranular em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 31 publications
4
93
1
1
Order By: Relevance
“…42), of which the tensile strength with and without impurities was examined. [42][43][44] At present we cannot conclude which one really exists, because both configurations lead to similar HRTEM images consistent with experimental observations. 41) In any case, both configurations have essential features common to other tilt GBs.…”
Section: Comparison With Other Ab Initio Resultssupporting
confidence: 47%
“…42), of which the tensile strength with and without impurities was examined. [42][43][44] At present we cannot conclude which one really exists, because both configurations lead to similar HRTEM images consistent with experimental observations. 41) In any case, both configurations have essential features common to other tilt GBs.…”
Section: Comparison With Other Ab Initio Resultssupporting
confidence: 47%
“…The lattice dimensions in the GB plane were fixed, neglecting Poisson's ratio to simplify the calculation. 10,[12][13][14]16) This step was repeated until GB fracture occurred. In each step, all atomic positions were optimized in accordance with Hellman-Feynman forces until all the forces were less than 0.03 eV/Å .…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Kohyama and coworkers 10,[12][13][14] studied various effects of impurities on the GB embrittlement in Al through the first-principles tensile tests. Yuasa et al 16) investigated the bond mobility mechanism in Fe with a P-segregated GB and they showed that the first bond breaking occurred at the Fe-P bond.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the BCC elements show the reduced size of the tetrahedral-shaped charge distribution, for example, BCC-Na shown in the fourth column of Figure 5, agreeing with previous observations that Na reduces the bond strength in interfaces. [56,57] In summary, the effect of 17 alloying elements on stacking fault energies of growth, deformation, and EFs in Mg is investigated through first-principles calculations. It is observed that all of them reduce the stacking fault energies of the deformation and EFs with La showing the least reduction for both.…”
mentioning
confidence: 99%